Evaluating Structural Changes in Graphite Under Ion Pulse Irradiation: A Case Study on Plasma Facing Materials - M.M.R. Seyed Habashy; A.R. Asle Zaeem (Journal of Advanced Materials in Engineering)
In this study, the effects of high-energy hydrogen ion irradiation, generated by the MTPF-2 type modern plasma focus device, on the surface and structural properties of graphite were investigated. High-energy protons produced by the plasma focus device were used to irradiate graphite samples in various shots. The radiation-induced changes on the graphite surface were examined using optical microscope and scanning electron microscopy. The modifications on the irradiated samples' surface were clearly observed in the scanning electron microscopyand optical microscope images. The microscopic images of the irradiated samples revealed point sputtering as well as pores on the sample surface, along with point melting, which are dependent on the ion fluence (number of shots). X-ray diffraction analysis was employed to study the structural changes in the graphite caused by the high-energy proton irradiation. The X-ray diffraction spectra of the irradiated samples showed shifts in the peak positions, changes in the peak intensities, and an increase in the crystallite size compared to the X-ray diffractionspectra of the reference sample. Additionally, a Faraday cup detector was used to characterize the hydrogen ion spectrum produced in the plasma focus device. The results indicated that the average energy of the generated ions was ~ 46 keV.